Penerapan Kedisiplinan dan Motivasi Belajar Santri Yang Tinggal di Dalam dan di Luar Pesantren Melalui Program Madrasah Diniyyah Pondok Pesantren Al-Ikhlas Tambakberas Jombang - Inggal Iksyaf Muttaqin; Penulis Imron Ariffin (Jurnal Ilmiah Wahana Pendidikan, 2022)
One of the popular perograms in Islamic Boarding School institutions is the Diniyyah Madrasah perogram. So that the surrounding community is interested in including their daughter's son to study at the institution. Therefore, it is necessary to apply appropriate discipline and motivation by the Madrasah institution of Pondok Pesantren Al-Ikhlas. So that this madin perogram can be continuous between satri who are mukim and non mukim. This study aims to (1) look at the discipline and learning motivation of mukim and non-mukim students (2) find out how the application of discipline and motivation is carried out by Madrasah Diniyyah (3) find out the supporting and inhibiting factors experienced by the Madin Pondok Pesantren Al institution. -Sincere. This research uses qualitative research with the type of case study research. While the method of data collection through observation, interviews, documentation. To analyze the data, the researcher used data reduction, data presentation and determining conclusions. To check the validity of using data credibility test and source triangulation. The results obtained (1) the discipline and learning motivation of non-mukim students are still lacking compared to mukim students (2) while the application of discipline is with discipline, sanctions, examples. While the application of motivation is by explaining the learning objectives, giving memorization and writing, the teacher has preparation before teaching, controlling, the takror program (3) supporting factors for the application of discipline all teachers and the surrounding community are involved. Meanwhile, there are still teachers and students who violate the rules. For factors supporting the application of motivation, namely the existence of daily control of the students. While the inhibiting factor is the lack of Madrasah Diniyyah institutions in collaborating with guardians of students, especially guardians of students who are non-mukim. Keywords: Application, Discipline, Motivation, Learning of Santri Mukim and Non Mukim